Progress toward the synthesis of providencin - Stevens, Sarah Jean, author; Wood, John L., advisor; Williams, Robert M., committee member; Kennan, Alan J., committee member; Kurosu, Michio, committee member; Rappé, Anthony K., committee member (Colorado State University. Libraries, 2011)
Providencin, a highly oxygenated diterpene, was isolated from the sea plume Pseudopterogorgia kallos in 2003 by Rodriguez and co-workers. Providencin was revealed to be a cembrane-based diterpene containing an unprecedented [12.2.0]hexadecane ring-system. Providencin was found to possess anti-cancer activity against human breast (MCF7), lung (NCI-H460) and CNS (SF-268) cancer cell lines. The unique structure and biological activity make providencin an attractive target for total synthesis and our work toward providencin began shortly after its isolation. The initial focus of each approach has centered on the unique trans-fused cyclobutanol moiety. A formal [2 + 2] cycloaddition is our chosen approach to the synthesis of the cyclobutane moiety. Further elaboration of our cyclobutane compounds has led to the synthesis of several highly functionalized intermediates. Our efforts toward the synthesis of providencin are discussed herein.
Keywords: [12.2.0]hexadecane; synthesis; Pseudopterogorgia kallos; providencin